The Quality of Hatching Egg and Development of Embryonic Somites in Kampung and Sentul Chickens - Muhammad Irsyad Zulfikar; Maria Ulfah; Mokhamad Fahrudin (Jurnal Ilmu-Ilmu Peternakan)
Kampung and Sentul chickens are Indonesian local chicken breeds that are widely developed by breeding companies as strains for meat production. The genetic differences among these chicken strains can impact the quality of the hatching eggs they produce. Somite development is a crucial part of chicken embryo growth during the hatching process, as it precedes the formation of vertebrae and skeletal muscles, ultimately affecting chick quality. This study aimed to analyse how both strains of hens affect hatching egg quality and somite development. The sample included 126 hatching eggs, with 63 from Kampung chickens and 63 from Sentul chickens. The observed parameters of hatching egg quality included egg weight, egg shape index, eggshell thickness, eggshell weight, eggshell strength, albumen index, yolk index, yolk color score, Haugh Unit (HU), and embryo development indicators, such as the development of the primitive streak and progression of somite number. The data were analysed using a t test. Differences between chicken strains significantly affected (P<0.05) egg weight, shell thickness, the albumen index, and HU. The different strains also showed significant differences (P<0.05) in embryo somite development, with the primitive streak development of the Sentul chicken being slower than that of the Kampung chicken. In conclusion, Kampung chickens produce hatching eggs with superior interior quality, primitive streak development and somite number compared to the hatching eggs of other chickens. However, Sentul chickens also demonstrate good exterior egg quality, as shown by their egg weight and shell thickness.